Chemokine Protocols - Proudfoot, Amanda E.I.; Proudfoot, Amanda E.I.; Wells, Timothy N.C.; Wells, Timothy N.C.; Power, Christine.; Power, Christine. (Methods in Molecular Biology, 2000)
In the past decade research has established the biological importance of chemokines: they play a major role in leukocyte trafficking, in the recruitment of leukocytes to inflammatory sites, and are coreceptors along with CD4 for HIV cell entry. In Chemokine Protocols, expert investigators describe in detail important techniques usedchemokine biology. Covering both ligands and receptors, these readily reproducible methods cover all aspects of chemokine research, ranging from the cloning and characterization of chemokines and their receptors, through the use of animal models to study chemokine function in vivo. Each method also includes relevant background information, as well as providing a useful bibliography that renders the study of chemokines accessible at all levels of experience. Comprehensive and highly practical, Chemokine Protocols offers experimental and clinical chemokine researchers today's gold-standard collection of proven methods for analyzing this biologically ubiquitous and important class of proteins.